A-site reconstruction perovskite oxide and preparation method and application thereof
The A-position of perovskite oxide is reconstructed by hydrolysis of alkoxide to form LaCoO3/La(OH)3 complex, which solves the problem that the A-position of the existing perovskite oxide catalyst does not directly participate in the catalytic reaction, and significantly improves the catalytic activity and ENR degradation efficiency.
Patent Information
- Application Number
- CN202411534252.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The A position of the existing perovskite oxide catalysts does not directly participate in the catalytic reaction, and have a small specific surface area, limiting the catalytic activity.
The A-position of perovskite oxide is reconstructed by alkoxide hydrolysis to form a LaCoO3/La(OH)3 complex, and La(OH)3 nanoparticles are embedded in the LaCoO3 surface to increase catalytic activity.
The catalytic activity is significantly improved, the adsorption and catalytic capacity of target pollutants is enhanced, and the PMS activation capacity and ENR degradation efficiency are improved.
Smart Images

Figure CN119588364A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite catalysts, and in particular to an A-site reconstructed perovskite oxide and a preparation method and application thereof. Background Art
[0002] Antibiotics are a class of drugs that kill or inhibit bacteria and are widely used to treat infectious diseases in humans and animals. However, due to the overuse and misuse of antibiotics, drug-resistant bacteria are rapidly emerging worldwide, seriously compromising their effectiveness. Antibiotics have also been identified as high-risk substances in global risk assessments of thousands of micropollutants. Because treatment plants are not sufficient to completely remove antibiotics, so that antibiotics still enter the aquatic environment, advanced treatment processes are urgently needed to effectively remove antibiotics.
[0003] Advanced oxidation processes (AOPs) have been developed as a powerful technology for the degradation of refractory organic pollutants by utilizing reactive oxygen species (ROSs). − , has strong oxidizing ability. 1 Non-free radicals such as O2 have high tolerance to various inorganic ions and organic matter. SO4• − and 1 O2 generation is usually derived from the activation of peroxymonosulfate (PMS) or peroxydisulfate (PDS) using various transition metal-based activators. Notably, cobalt-based catalysts exhibit excellent PMS / PS activation performance, which is attributed to the Co 2+ 's specific 3d band structure. Among these catalysts, cobalt-based perovskite oxides have become the rising star of multi-metal catalysts due to their high design flexibility, tunable surface properties and stability. However, it has been reported that the A site of perovskite oxides is not directly involved in the catalytic reaction. In addition, perovskite oxides themselves have a small specific surface area, which limits the exposure of the catalytically active B site of perovskite oxides. Currently, doping, defects, interface engineering and nanoengineering are widely used to improve the catalytic activity of perovskite oxides, while research on the modification of the A site of perovskite oxides is limited. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide an A-site reconstructed perovskite oxide to address the deficiencies of the prior art. The A site of the perovskite oxide is reconstructed by hydrolysis of alcohol salts, and the inactive A site of the perovskite oxide is converted into an active center, which significantly improves the catalytic activity and provides new ideas for future material design and heterogeneous AOPs research.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A site A reconstructed perovskite oxide, wherein the perovskite oxide is a LaCoO3 / La(OH)3 complex, and the La(OH)3 nanoparticles are uniformly embedded in the surface of LaCoO3.
[0006] A method for preparing A-site reconstructed perovskite oxide comprises the following steps: (1) Add LaCoO3 to a solvent of glycerol and isopropanol under stirring; (2) The above solution is then transferred to an autoclave and heated at 180°C for 0.5-4h to form lanthanum alkoxide as a precursor of La(OH)3; (3) Wash with ethanol and distilled water in sequence, disperse in deionized water, and then transfer the suspension into an autoclave, heat at 160 °C for 0.5-6 h, cool to room temperature, wash the precipitate, and dry it.
[0007] Furthermore, in step (1), the ratio of LaCoO3, glycerol and isopropanol is 0.3 g: 15-25 mL: 55-65 mL.
[0008] Furthermore, the LaCoO3 is prepared by the following steps: (1) La(NO3)3 and Co(NO3)2 were added to deionized water, and after magnetic stirring for 0.5-1 hour, EDTA and citric acid were added to the above solution, wherein the molar ratio of La(NO3)3, Co(NO3)2, EDTA and citric acid was 1:1:2:4; (2) Stir the solution vigorously and heat it to 90 °C in a water bath. Evaporate the mixed solution until a purple gel is obtained and dry it for 12 h. (3) grinding and calcining the obtained brown spongy solid to obtain a product; Furthermore, the calcination in step (3) is divided into two stages, at 5°C min -1 The temperature was raised to 200 °C for 1 h, and then heated at 10 °C min -1 The temperature was raised to 900°C and calcined for 6 hours.
[0009] Application of A-site reconstructed perovskite oxide in catalytic degradation of ENR.
[0010] Further, the application conditions are: ENR concentration is 10mg·L -1 The catalyst dosage is 0.1 g·L -1 , [PMS] dosage is 0.05-0.3 g·L -1 , the temperature is 295-310K.
[0011] Furthermore, the application conditions are: ENR concentration is 10 mg·L -1 The catalyst dosage is 0.1 g·L -1 , [PMS] dosage is 0.2 g·L -1 , the temperature is 300K.
[0012] Furthermore, the A-site reconstructed perovskite oxide is loaded on a PVDF substrate to prepare a catalytic membrane for catalytic degradation of ENR, and the ENR solution is degraded through the catalytic membrane by external pressure.
[0013] Furthermore, the catalyst loading is 5-10 mg, and the flux is 26.45-264.52 L / (m 2 h).
[0014] The beneficial effects of the present invention are: 1. The present application develops an A-site reconstructed perovskite oxide LaCoO3 / La(OH)3 composite, in which the (210) crystal plane of La(OH)3 is in close contact with LaCoO3 to form a heterojunction, La(OH)3 nanoparticles are uniformly embedded in the surface of LaCoO3, and the weight ratio of LaCoO3 to La(OH)3 is 7-9:1.
[0015] 2. The present application reconstructs the A site of the perovskite oxide by hydrolysis of alcohol salts. First, a sponge-like LC (LaCoO3) is prepared by a sol-gel method. Then, glycerol and isopropanol are added. First, alcoholization is carried out under high temperature and high pressure, and alkoxide lanthanum is formed as a precursor of La(OH)3 through a solvothermal reaction. Then, hydrolysis is carried out at high temperature and high pressure, so that La(OH)3 can slowly grow onto the surface of LaCoO3 through hydrolysis, thereby realizing the modification and reconstruction of the A site of the perovskite oxide. The preparation process is simple and easy to realize large-scale application.
[0016] The reconstruction of the A site increases the specific surface area of the catalyst, thereby increasing its adsorption of target pollutants; the reconstruction of the A site changes the electronic structure of LC, enhances the electronic activity of the La-f orbital, and the formation of the Co-O-La bridge bond provides a channel for the transfer of electrons from LC to La(OH)3, thereby improving the conductivity of the material; the inactive La sites of the perovskite oxide are converted into active centers, increasing the types of active sites; the La and Co sites jointly serve as active sites for PMS activation; compared with LC with a single Co active site, the PMS activation ability and ENR degradation efficiency of LC24 are increased by 4.5 times.
[0017] 3. The prepared product was characterized by XRD. During the surface reconstruction process, La(OH)3 was gradually formed on the LC surface. The FTIR results showed that lanthanide alkoxides may have been formed during the reaction. SEM characterization showed that during the reconstruction of the A site, nanoparticles aggregated on the product surface. As the alkoxide time increased, La(OH)3 was successively regenerated on the LC surface. The interface structure can be clearly observed by TEM. LC24 showed obvious lattice diffraction stripes, indicating that a heterojunction structure was formed. Moreover, X-ray diffraction Rietveld analysis showed that the ratios of LC and La(OH)3 in LC24 were 89.04% and 10.96%, respectively. After the reconstruction of the A site, the BET specific surface area of LC24 increased from 2.5698m² / g of LC to 13.1377m² / g. The specific surface area was greatly increased, and more active sites were exposed, which was more conducive to increasing the catalytic reaction. XPS analysis showed that there was electron redistribution and strong interfacial interaction between La(OH)3 and LC. After reconstruction, La(OH)3 in LC24 2+ The ratio of La relative to the total La increased to 60.00%, i.e., reconstruction of the A site of LC24 could adjust the electronic structure of LC and enhance the electronic activity of La-f orbitals.
[0018] 4. The mechanism of the A-site reconstruction of perovskite oxide catalytic degradation of ENR in this application is: PMS adsorbed on the LC24 heterogeneous interface is activated to SO4• − and 1 O2, the piperazine and quinolone rings of ENR are susceptible to electrophilic attack and are initially attacked by SO4• − and 1 O2 attacks and gradually decomposes into small molecules (CO2, H2O, NO3 - and F - ).
[0019] 5. In the application experiment, the degradation efficiency of LC26 (alcoholization time 2h, hydrolysis time 6h) on ENR can reach 99.89% (k obs =0.754min -1 ), showing high catalytic activity.
[0020] 6. In addition, the present application also constructs an LC24 micro-catalytic membrane reactor, using vacuum assistance to closely stack the catalyst on the PVDF membrane to form a complex channel, providing a local space for ENR degradation. obs The value reaches 441.34 min -1 , which is better than the conventional heterogeneous LC24 / PMS system (0.702 min -1) was four orders of magnitude higher, and under the conditions of catalyst loading of 10 mg and water flux of 26.45 LMH, the LC24 membrane / PMS system degraded 96.26% of enrofloxacin. The rapid activation of PMS in the intramembrane channel and the nearly complete degradation of ENR were achieved within a short retention time of 9.67 ms. After 12 hours of continuous operation, the efficiency of ENR decomposition remained above 96.26%, and the system stability was very strong.
[0021] This study not only provides new design guidance for regulating the active centers of catalytic materials through structural reconstruction, but also broadens the application of perovskite oxide-based catalytic membrane reactors in environmental remediation. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 : Schematic diagram of the synthesis of LC and LC24 (a), XRD spectrum of LC prepared in Example 1 and XRD spectrum of oxides prepared with hydrolysis time of 4h and different alcoholization time (b), FTIR spectra of different materials (c); XRDRietveld spectrum of LC24 (d); HR-TEM image of LC24 (e); EDS image of LC24 (f); Nitrogen adsorption and desorption isotherms of LC and LC24 (g).
[0023] Figure 2 : High-resolution spectra of La 3d (a), Co 2p (b), and O 1s (c) in LC and LC24, and DOS diagrams of La(OH)3 (d), LC (e), and LC24 (f).
[0024] Figure 3 : Degradation curves of ENR by oxides prepared with different alcoholization time (a, hydrolysis time is 4h) and different hydrolysis time (b, alcoholization time is 2h) and LC; k of ENR degradation by different alcoholization and hydrolysis time obs Value (c); Degradation curves of ENR with different PMS doses in LC / PMS (d) and LC24 / PMS (e) systems; k obs Value (f); Degradation curves of ENR in LC / PMS (g) and LC24 / PMS (h) systems at different temperatures and apparent activation energy (i). Conditions: ENR = 10 mg / L, catalyst = 0.1 g / L, PMS = 0.2 g / L, initial pH = 6.65, T = 27°C.
[0025] Figure 4: Schematic diagram of the catalytic membrane reactor (a); Degradation diagram of ENR in the LC24 membrane / PMS system at different catalyst loadings and different fluxes (b); Absorbance of PMS in the LC24 membrane / PMS system at different reaction times (c); Continuous degradation curve of ENR in the LC24 membrane / PMS system (d); Effect of inorganic ions on the degradation of ENR in the LC24 membrane / PMS system (e); Adsorption energy of PMS on LC (f); Adsorption energy of PMS on LC24 (g).
[0026] Figure 5 : The alcoholysis time is 2h, and the XRD patterns of the oxides prepared at different hydrolysis times.
[0027] Figure 6 : XRD patterns of La(OH)3, Co3O4 and LC-AS.
[0028] Figure 7 : SEM images of (a) LC, (b) al0.5, (c) al2, (d) al4, and (e) al6.
[0029] Figure 8 SEM images of: (a) LC, (b) hy0.5, (c) hy2, (d) hy4, (e) hy6, (f) La(OH)3, and (g) Co3O4.
[0030] Fig. 9 : TEM spectrum of LC24.
[0031] Fig.10 : High-resolution XPS patterns of LC and LC24.
[0032] Fig.11 : Electron density difference map at the LaCoO3 / La(OH)3 interface; the dark yellow and cyan regions indicate charge accumulation and depletion, respectively.
[0033] Fig.12 :Adsorption curves of LC, LC24, and La(OH)3 for NER.
[0034] Fig.13 :Degradation curves of NER in different reaction systems, where: [enrofloxacin] = 10 mg·L -1 ,[catalyst] = 0.1 g·L -1 , [PMS] = 0.2 g·L -1 , initial pH = 6.65, T = 27 ℃.
[0035] Fig.14 : The first-order kinetic fitting curves of LC degradation of ENR at different alcoholization times.
[0036] Fig.15 : The first-order kinetic fitting curves of LC degradation of ENR at different hydrolysis times.
[0037] Fig.16 : The first-order kinetic fitting curves of ENR degradation in LC / PMS system with different PMS doses.
[0038] Fig.17 : The first-order kinetic fitting curves of ENR degradation in LC24 / PMS system with different PMS doses.
[0039] Fig.18 : The first-order kinetic fitting curves of LC / PMS degradation of ENR at different temperatures.
[0040] Fig.19 : The first-order kinetic fitting curves of ENR degradation in LC24 / PMS system at different temperatures.
[0041] Fig. 20 :k at different temperatures in LC / PMS and LC24 / PMS systems obs value.
[0042] Fig.21 : The absorbance of PMS in LC / PMS system with different reaction times.
[0043] Fig. 22 : Activation rate of PMS in LC / PMS and LC24 / PMS systems.
[0044] Fig.23 : The absorbance of PMS in LC24 / PMS system at different reaction times.
[0045] Fig.24 : The first-order kinetic fitting curve of ENR degradation in LC24 membrane / PMS system.
[0046] Fig.25 : Activation rate curves of PMS in LC24 / PMS and LC24 membrane / PMS systems.
[0047] Fig.26 : XRD patterns of LC24 before and after use.
[0048] Fig. 27 : High-resolution XPS images of LC24 before and after use.
[0049] Fig.28 :Effects of inorganic ions on ENR degradation in LC24 / PMS system.
[0050] Fig.29 : Degradation curve of ENR in lanthanum-based catalyst reaction system.
[0051] Fig.30 : The absorbance of PMS in La(OH)3 / PMS system at different reaction times.
[0052] Fig.31 : Activation rate curve of PMS in La(OH)3 / PMS system.
[0053] Fig.32 : pH change curves in La(OH)3 / PMS, LC24 / PMS and LC / PMS systems. DETAILED DESCRIPTION
[0054] The present invention is further described below in conjunction with the accompanying drawings and examples. In the following examples, the prepared LaCoO3 is referred to as LC, and LCxy refers to oxides prepared with different alcoholization times (x) and different hydrolysis times (y), wherein the A-site reconstructed perovskite oxide LaCoO3 / La(OH)3 complex prepared in Example 1 is referred to as LC24. The product prepared in Example 3 that only undergoes alcoholysis is referred to as LC-SA. Example 1
[0055] An A-site reconstructed perovskite oxide is a LaCoO3 / La(OH)3 composite, wherein La(OH)3 nanoparticles are uniformly embedded on the surface of LaCoO3. The specific preparation method thereof comprises the following steps: (1) 0.3 g of LaCoO3 was added to a solvent containing 20 mL of glycerol and 60 mL of isopropanol under stirring for 0.5 h; (2) The above solution was then transferred to an autoclave and heated at 180 °C for 2 hours (alcoholization) to form alkoxylanthanum as a precursor of La(OH)3 through a solvothermal reaction; (3) The sample was washed three times with ethanol and distilled water in sequence and finally dispersed in 30 mL of deionized water. The suspension was then transferred to an autoclave and heated at 160 °C for 4 h (hydrolysis). During the hydrothermal process, La(OH)3 could slowly grow onto the surface of LaCoO3 by hydrolysis. After cooling to room temperature, the precipitate was washed and dried to obtain LC24.
[0056] The above LaCoO3 is prepared by the following steps (see Figure 1 a): (1) Add 6 mmol La(NO3)3 and 6 mmol Co(NO3)2 into a beaker containing 50 mL deionized water. After magnetic stirring for 0.5 h, add 12 mmol EDTA and 24 mmol citric acid to the solution. (2) Stirring the solution vigorously and heating it to 90°C in a water bath, evaporating the mixed solution until a purple gel is obtained, and immediately drying it in a drying oven at 130°C for 12 h; (3) The brown spongy solid obtained was ground and calcined in two stages: calcined at 200 °C for 1 h (5 °C min −1 ), followed by calcination at 900 °C for 6 h (10 °C min -1 ), LC (LaCoO3) was obtained.
[0057] Embodiment 2-5 The hydrolysis time in step (3) is 4 h, and the alcoholization time in step (2) is adjusted to 0.5 h (al0.5) , 2h (al2), 4h (a4), 6h (al6), and other processes are the same as those in Example 1.
[0058] Embodiment 6-9 The alcoholization time in step (2) is 2 h, and the hydrolysis time in step (3) is adjusted to hy0.5, hy2, hy4, and hy6, respectively. The other processes are the same as in Example 1.
[0059] Comparative Example 1 The steps for preparing LC-SA are: (1) 0.3 g of LaCoO3 was added to a solvent containing 20 mL of glycerol and 60 mL of isopropanol under stirring for 0.5 h; (2) The above solution was then transferred into an autoclave and heated at 180 °C for 2 h. The precipitate was washed and dried to obtain LC-SA.
[0060] That is, LC-SA is a product prepared by treating LC with glycerol and isopropanol at high temperature and high pressure, directly washing and drying, and no longer undergoing a hydrolysis reaction.
[0061] Comparative Example 2 Preparation of La(OH)3: 0.3 g of LaCoO3 in Example 1 was replaced by 0.3 g of La(NO3)3, and other processes remained unchanged. The prepared product was La(OH)3.
[0062] 1. Performance Testing 1. XRD characterization X-ray diffraction (XRD) Figure 1b) shows that the LC prepared in Example 1 has good crystallinity, which is consistent with LaCoO3 (JCPDS No. 84-0848). The main diffraction peaks at 2θ = 23.235, 32.886, 33.298 and 47.501° correspond to the (110), (-110), (112) and (220) crystal planes, respectively.
[0063] When the hydrolysis time is 4 hours, Examples 2-5 study the effect of different alcoholization times on the LC structure. Figure 1 As shown in b, 0.5 h has the least effect on the crystal structure of LC. When the reaction time is extended to 2 h (al2), a new set of diffraction peaks related to La(OH)3 (JCPDS No. 83-2034) are located at 15.616, 27.220, 27.970 and 39.425°, which are attributed to the (100), (110), (101) and (201) crystal planes, respectively. As the reaction time increases to 4 h (al4), the intensity of the diffraction peaks of La(OH)3 increases. In addition, additional peaks corresponding to Co3O4 (JCPDS No. 76-1802) begin to appear at 36.266° and 36.840°. After 6 h (al6), the intensity of the characteristic diffraction peaks of La(OH)3 and Co3O4 is further enhanced, while the characteristic peaks of LC weaken with the increase of reaction time. Given that La-O bonds are weaker than Co-O bonds, under high temperature, high pressure and weakly acidic conditions of alcohol, La-O chains are preferentially broken to form lanthanide alkoxides, which are then hydrolyzed into lanthanum hydroxide. As the reaction time increases, the La-O bonds on the surface are reconstructed, while the Co-O octahedral structure retained by LC forms Co3O4.
[0064] Meanwhile, Examples 6-9 studied the effect of different hydrothermal times on the LC structure, such as Figure 5 As shown in Figure 2, when the alcoholization time is fixed at 2 hours, the hydrothermal time (hy0.5-hy6) affects the formation of La(OH)3. The trend is that the La(OH)3 content gradually increases and becomes relatively stable after 4 hours. The XRD spectra of pure La(OH)3 and Co3O4 are shown in Figure 2. Figure 6 These XRD results indicate that La(OH)3 and Co3O4 are gradually formed on the LC surface during the surface reconstruction process.
[0065] 2. FTIR detection FTIR was used to track the A-site reconstruction process ( Figure 1 c). 3430 cm -1 and 1636 cm -1 The band at 560 cm-1 can be attributed to the OH vibration of water adsorbed on the surface of samples LC, LC24, LC-AS and La(OH)3. -1The energy band observed at 3320 cm-1 is characteristic of the Co-O stretching vibration mode. -1 The OH stretching vibration peak of alcohol is shown at 2924 cm -1 The symmetrical stretching vibration peak of CH3 is at 1457 cm -1 The bending vibration peak of CH3 at 1120 cm -1 The LC-AS is a sample that has only been treated with alcohol and inherits most of the characteristic peaks of AS (2924 cm -1 、1457cm -1 , 1120 cm -1 ). The results show that there is a strong interaction between alcohol and LC. The peak at 1408 cm was also observed in LC24 and La(OH)3 -1 There is a CO stretching vibration peak at , which may be due to the interaction between surface La(OH)3 and atmospheric CO2. These FTIR results suggest that lanthanide alkoxides may be formed during the reaction.
[0066] 3. SEM characterization Figure 7 Scanning electron microscopy (SEM) in showed that LC had good dispersion with a particle size of 300-500nm and a smooth surface with a bean-like morphology. The surface of sample al0.5 became rough, probably due to the breaking of La-O bonds. The generation of nanoparticles with an average size of approximately 100nm was observed on the surface of sample al2, which was attributed to the reconstruction of the A site. It was observed that the surface of sample al4 exhibited a high degree of nanoparticle aggregation. Nevertheless, the original bean-like appearance of LC was retained. In sample al6, further alcoholization led to the appearance of nanosheets with nanoparticles interspersed therein. For these samples hy0.5-hy6, from the SEM images ( Figure 8 ) It can be seen that the roughness of the LC surface and the surface nanoparticles have increased. Figure 8 As shown in Figures 8f and 8g, the SEM images show that the original La(OH)3 and Co3O4 have nanoparticle and nanosheet structures, respectively. These SEM results are consistent with the XRD analysis, and La(OH)3 and Co3O4 are successively regenerated on the LC surface with the increase of alcoholization time.
[0067] 4. X-ray diffraction Rietveld full spectrum fitting analysis, HR-TEM and specific surface area detection The XRD full spectrum fitting method was used to accurately determine the content of each phase of LC24. The LaCoO3 / La(OH)3 polycrystal was refined using the R-3cH and P63 / m space group models. The refinement results of LC24 are shown in Figure 1d and Table 1, indicating that the sample fit is very high (Rwp = 3.34%, Rp = 2.4%, χ 2 =2.14). These results indicate that the ratios of LC to La(OH)3 in LC24 are 89.04% and 10.96% (i.e., 8.12:1), respectively. The interfacial structure can be clearly observed by transmission electron microscopy (TEM) images ( Fig. 9 ), high-resolution TEM (HR-TEM) images show that LC24 exhibits obvious lattice diffraction fringes ( Figure 1 e), the lattice distance of 0.2140nm corresponds to the (210) crystal plane of La(OH)3, which is in close contact with LaCoO3 to form a heterojunction. In addition, energy dispersive spectroscopy (EDS) mapping was performed, revealing that the distribution of La, Co, and O elements is uniform ( Figure 1 f). In addition, after reconstruction of the A site, LC24 showed a type III isotherm with a hysteresis loop, and the BET surface area increased from 2.5698 m² / g in LC to 13.1377 m² / g ( Figure 1 g). The increase in specific surface area means that the adsorption characteristics are enhanced and more active sites are exposed.
[0068] Table 1. X-ray diffraction Rietveld analysis of LC24
[0069] 5. XPS detection The surface elemental composition and chemical state of LC and LC24 were studied by X-ray photoelectron spectroscopy (XPS). Fig.10 In the high-resolution La 3d spectrum, the two pairs of peaks of LC correspond to La 2+ 834.07 eV and 850.67 eV and La 3+ 837.74 eV and 854.36 eV ( Figure 2 a). Figure 2 In the high-resolution Co 2p spectrum in b, the peaks at 780.03 eV and 795.15 eV correspond to Co 3+ , the peaks at 782.01 eV and 790.67 eV correspond to Co 2+ In the high-resolution O 1s spectrum ( Figure 2 c), the peaks at 529.02 eV, 531.35 eV, and 532.56 eV are assigned to lattice oxygen (O I ), highly oxidative oxygen species (O II ) and surface adsorbed oxygen species (O III). Importantly, it is found that by normalization, Co 2+ / (Co 3+ +Co 2+ ) ratio is LC (31.05%) > LC24 (28.88%). 2+ The ratio relative to the total La increased to 60.00% (LC (52.81%)). The results indicate that there is electron redistribution and strong interfacial interaction between La(OH)3 and LC.
[0070] To elucidate the interfacial interactions, the charge density distribution at the LC24 interface was investigated by DFT calculations. The Fermi level intersects the total density of states of La(OH)3, LC, and LC24, indicating that all components retain metallic properties. Figure 2 d) and LC ( Figure 2 e) Compared with LC24 ( Figure 2 f) increases in the intensity of the total density of states (DOS), leading to an increase in the number of conductive carriers in the composite. Therefore, the interfacial properties effectively enhance the conductive properties of LC24. A systematic analysis of the projected density of states (PDOS) was performed to evaluate the changes in energy states. For pristine La(OH)3 and LC, the band gap between the La-f and Op orbitals indicates a weak interaction between the La-O bonds. In contrast, the La-f orbital of LC24 is close to the Fermi level, while the band gap gradually disappears. Therefore, the La-f and Co-p orbitals overlap with the Op orbital to form a La-O-Co bridge bond, providing a channel for interfacial electron transfer. The charge transfer was quantified by charge density difference and Bader topological analysis. Fig.11 In the figure, the charge accumulation region is drawn in yellow and the charge depletion region is drawn in cyan, resulting in an obvious redistribution of electrons at the interface after LC24 formation. - The electrons are transferred from each LC protocell to La(OH)3, resulting in the accumulation of electrons on La(OH)3. The calculated results are consistent with the XPS analysis, which shows that La 2+ Therefore, reconstruction of the A site of LC24 can adjust the electronic structure of LC and enhance the electronic activity of La-f orbital. The formation of Co-O-La bridge bonds provides a channel for electrons to transfer from LC to La(OH)3, thereby improving the conductivity of the material.
[0071] 2. Application Experiment 1 10 mg of enrofloxacin (ENR) was dissolved in 1 L of deionized water to prepare the enrofloxacin solution. 50 mL of the enrofloxacin solution was measured and placed in a three-necked round bottom, and then 5 mg of the catalyst was added to the solution and mechanically stirred for 30 minutes to establish the adsorption-desorption equilibrium. Subsequently, 200 μL of 50 g / L PMS was added to start the reaction. At certain time intervals, 1 mL of the suspension was taken out and immediately mixed with 100 μL of methanol pre-filled in a centrifuge tube to quench any possible reaction. The catalyst was filtered through a 0.22 μm nylon filter membrane and the filtrate was collected in a sample bottle. The initial pH of the reaction system was about 6.65, and the pH was subsequently adjusted by adding diluted KOH and H2SO4. The used catalyst was recovered by filtration, washing and drying. C0 (mg / L) and C t (mg / L) are the initial and reaction time t ENR concentrations, respectively; k obs (min -1 ) is the reaction rate constant; t (min) is the reaction time.
[0072] Compared with LC (13.25%), LC24 and La(OH)3 showed better adsorption performance for ENR, with the adsorption rates of 20.22% and 19.69%, respectively ( Fig.12 ). This enhanced performance is attributed to the excellent adsorption capacity of La(OH)3. Fig.13 It showed that only 4.77% of ENR was decomposed by PMS, and the removal efficiency of ENR by LC was 69.20% within 8 min. Figure 3 The effect of aging time on degradation performance was studied. With the increase of aging time, the degradation performance first increased and then weakened ( Figure 3 a), the corresponding k obs The value changes like a volcano ( Figure 3 c and Fig.14 When the alcoholization time is set to 2 hours, the optimal degradation efficiency is 98.71% (k obs =0.702 min -1 ), which is attributed to the in situ reconstruction of the LC surface to form La(OH)3. Pure La(OH)3 was shown to participate in the degradation of ENR by PMS activation with a degradation efficiency of 91.96% ( Fig.13 However, after 1 min of reaction, the power of pure La(OH)3 was obviously insufficient. The degradation efficiency decreased with the extension of alcoholization time due to the formation of Co3O4. Co3O4 ( Fig.13 ) has an intrinsic activity of 13.61%, which is lower than that of La(OH)3, and its formation rather masks other active sites. With the increase of hydrolysis time, the degradation performance of ENR gradually increased from 82.36% to 99.89% ( Figure 3 b) reaches a steady state at 4 hours, k obsThe value increased from 0.199 to 0.754 min -1 , which is consistent with the effect of hydrolysis time on the surface La(OH)3 content ( Figure 3 c and Fig.15 ). Considering the cost and performance, the optimal alcoholization and hydrolysis times were 2h and 4h, respectively, and the prepared product was LC24.
[0073] The catalytic activities of LC and LC24 were systematically studied at different PMS doses and temperatures. Increasing the PMS dose from 0.05 g / L to 0.30 g / L improved the degradation efficiency of the LC / PMS system from 41.69% to 82.05% ( Figure 3 d). This increase is accompanied by k obs The corresponding increase in the value, from 0.09 to 0.214 min -1 ( Figure 3 f and Fig.16 ). Under similar conditions, the degradation efficiency of the LC24 / PMS system was significantly increased from 82.34% to 99.65% ( Figure 3 e), k obs The value increased from 0.362 to 0.897min -1 ( Figure 3 f and Fig.17 ). Compared with LC, the reaction kinetics of LC24 was improved by 3.6-4.5 times, indicating that the A-site reconstruction of LC effectively improved the mass transfer efficiency at the heterogeneous interface. Activation energy (Ea) is also an important factor in the characterization of chemical reaction kinetics. External heating (295-310K) improved the degradation efficiency of LC / PMS and LC24 / PMS systems to varying degrees ( Figure 3 gh). k for LC / PMS system obs The value increased from 0.085 to 0.338 min -1 ( Figure 17-20 ), a parallel increase was observed in the LC24 / PMS reaction system, from 0.361 to 1.382 min -1 By fitting k at different temperatures obs The value is determined by (Ea). Figure 3 h shows that the Ea value of LC24 is 65.709 KJ / mol, which is less than that of LC (69.247 KJ / mol), indicating that the energy barrier is lower and the reaction is easier to complete. The difference between the LC / PMS and LC24 / PMS systems in eliminating ENR is related to the ability of PMS to activate. In the LC / PMS system, the PMS concentration changes the least before and after the reaction ( Fig.21 ), the activation rate of PMS is only 12.83% ( Fig. 22 In contrast, the PMS concentration of the LC24 / PMS system changed significantly ( Fig.23 ), of which 57.31% of PMS were activated. Therefore, the enhanced activation of PMS is responsible for the rapid degradation of ENR in the LC24 / PMS system.
[0074] 3. Application Test 2 Design a microcatalytic membrane reactor (see Figure 4 a). The catalyst is stacked closely on the PVDF membrane using vacuum assistance to form complex channels, providing local space for ENR degradation. Since the pollutant solution does not easily pass through the catalytic membrane spontaneously, external gas pressure is used to force the solution through and adjust its flux. The specific operation method is: LC24 was dispersed in 20 mL of distilled water and continuously sonicated for 1 hour. Under vacuum conditions, the LC24 catalytic membrane was prepared by direct filtration onto a PVDF substrate (diameter 47 mm, pore size 0.45 μm). The catalytic membrane was then supported by a stainless steel grid and sealed in a micro-integrated stainless steel support. The complete catalytic membrane reactor consists of an air compressor, a pressure regulator, a liquid storage tank, and a catalytic membrane support connected in series (see Figure 4 a). ENR and PMS water flow through the catalytic membrane driven by gas pressure. Table 2 lists the relevant experimental parameters.
[0075] Flux through LC24 membrane: J=V q / (S m ×T), J ((L / (m 2 h)), LMH) represents the flux; Vq (L) is the volume of the filtered solution; Sm (m 2 ) is the effective filtration area of the membrane; T (h) is the permeation time.
[0076] Calculate the retention time (t, ms) in the LC film: t = (3600V m ×m) / (J×S m ), where V m (cm 3 / g) is the pore volume of LC24, m (g) is the total mass of catalyst loaded, J (LMH) is the water flux, S m (m 2 ) is the effective membrane filtration area, and T (h) is the permeation time.
[0077] Table 3 lists the retention time of the ENR solution passing through the catalytic membranes with different catalyst loadings and different fluxes.
[0078] Table 2. Experimental parameters of the reactor
[0079] Table 3. Retention time of ENR solution passing through catalytic membranes with different catalyst loadings and fluxes
[0080] The solution flux was adjusted within the range of 26.45-264.52 LMH, such as Figure 4 As shown in (b), the degradation efficiency of ENR was positively correlated with the catalyst loading (ENR concentration was 10 mg / L). The catalytic membrane with a catalyst loading of 5 mg operated at a fluid flux of 26.45 LMH showed an ENR degradation efficiency of 89% and a retention time of 4.84 ms (Table 3). It is worth noting that the k obs The value reaches 441.34 min -1 ( Fig.24 ), which is lower than the conventional heterogeneous LC24 / PMS system (0.702 min -1 ) was four orders of magnitude higher, indicating that the catalytic membrane has a stronger ability to degrade ENR. Under the conditions of a catalyst loading of 10 mg and a water flux of 26.45 LMH, the LC24 membrane / PMS system degraded 96.26% of enrofloxacin, and the rapid activation of PMS in the intramembrane channel and the nearly complete degradation of ENR were achieved within a short retention time of 9.67 ms. In addition, it was observed that the activation rate of PMS in the LC24 membrane / PMS system reached 58.30% ( Figure 4 c and Fig.25 ). The results show that the local space of the catalytic membrane can improve the mass transfer efficiency and the utilization rate of free radicals. After 12 hours of continuous operation, the efficiency of ENR decomposition remained above 96.26% ( Figure 4 d). Therefore, the LC24 membrane / PMS system exhibits stable and efficient performance for the degradation of ENR. At the same time, the XRD spectrum of the reaction LC24 shows the characteristic peaks of LC and La(OH)3, and no other peaks are detected ( Fig.26 ). The XPS spectrum of the reaction LC24 shows that the intensity of the characteristic peaks of La, Co, and O elements is weakened, and the intensity of the C peak is significantly enhanced, which is due to the adsorption of ENR or its intermediates on the surface of the reaction LC24 ( Fig. 27 ). These findings suggest that LC24 has a robust structure.
[0081] 4. Interference Experiment Simulate the effect of inorganic ions in actual wastewater on the LC24 membrane / PMS system. Figure 4 As shown in e, adding NO3 - 、H2PO4 - and Cl - There was no significant effect on the LC24 membrane / PMS system. On the contrary, it was found that HCO3 -The presence of (4-20 mM) significantly hindered the degradation of ENR, reducing the removal efficiency by 41.96% to 26.98%. This finding is consistent with the established interference effect of inorganic ions on traditional suspension systems ( Fig.28 ). This phenomenon is similar to HCO3 - Can attack SO4• − and produce less reactive carbonate radicals (HCO3•, CO3• − The results show that the LC24 membrane / PMS system has a certain resistance to inorganic ions.
[0082] 5. Mechanism Study Identification of active sites on the catalyst surface. It has been reported that the B site of perovskite oxides often acts as the main active site, while the A site is not directly involved in the catalytic reaction. However, after reconstruction of the A site, it was found that LC24 significantly enhanced the degradation of ENR, so it is necessary to study the role of La(OH)3. La(OH)3 is commonly used as an adsorbent for recovering phosphate from aquatic environments, and it has superior adsorption performance for ENR compared to LC ( Fig.13 ). This enhanced adsorption of La(OH)3 contributes to the improved catalytic performance of LC24. Fig.29 As shown, La 3+ The degradation performance of the / PMS system to ENR is consistent with that of the PMS system alone, indicating that La 3+ PMS is not activated. However, in the La2O3 / PMS and La(OH)3 / PMS systems, the degradation efficiency of ENR is 35.38% and 91.96%, respectively. This finding indicates that lanthanum oxide / hydroxide can promote the activation of PMS and thus degrade ENR, where La(OH)3 can activate 17.92% of PMS in the reaction system ( Figure 30-31 In particular, the initial pH of the dispersion of La(OH)3 in ENR solution was 7.40, which was higher than that of LC (pH 6.43) and LC24 (pH 6.65). When PMS was added to initiate the reaction, the pH values of the La(OH)3 / PMS, LC / PMS, and LC24 / PMS systems were stabilized at around 5.50, 3.70, and 4.00, respectively ( Fig.32 ). It has been reported that alkali was used as a novel activator for PMS. The excellent degradation performance of La(OH)3 was also attributed to its alkaline effect. In summary, La(OH)3 not only promoted the adsorption of ENR but also played a role in the activation of PMS. As determined by XRD refinement, when LC and La(OH)3 were physically mixed, the resulting degradation efficiency was 49.69%, which was lower than that of the LC24 / PMS system. The enhanced catalytic performance of LC24 was related to the formation of a heterojunction with strong interactions and electron transfer between the Co-O-La covalent bonds.
[0083] To gain insight into the catalytic mechanism of PMS activation at the LC24 interface, DFT calculations were used to evaluate the adsorption energy. Three potential adsorption sites were considered, namely the top sites of La, Co, and O positions. After structural optimization, the two oxygen atoms on PMS were always adsorbed on the Co-Co bridge site of LC with an adsorption energy of -2.22 eV ( Figure 4 f). Similarly, after structural optimization, the two oxygen atoms on PMS are always adsorbed on the La-Co bridge site of LC24, resulting in a significantly stronger adsorption energy of -4.06 eV ( Figure 4 g). This indicates that La and O sites are not stable adsorption sites for PMS on LC, while Co-Co bridge sites are stable. In contrast, the best adsorption site for LC24 is the La-Co bridge site. The results show that the heterojunction formed by LC and La(OH)3 is more stable for the adsorption of PMS, and La and Co sites together behave as active sites for LC24.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. An A-site reconstructed perovskite oxide, characterized in that: The perovskite oxide is a LaCoO3 / La(OH)3 complex, and the La(OH)3 nanoparticles are uniformly embedded in the surface of LaCoO3.
2. A method for preparing the A-site reconstructed perovskite oxide according to claim 1, characterized in that: The following steps are involved: (1) Add LaCoO3 to a solvent of glycerol and isopropanol under stirring; (2) The above solution is then transferred to an autoclave and heated at 180°C for 0.5-4h to form lanthanum alkoxide as a precursor of La(OH)3; (3) Wash with ethanol and distilled water in sequence, disperse in deionized water, and then transfer the suspension into an autoclave, heat at 160 °C for 0.5-6 h, cool to room temperature, wash the precipitate, and dry it.
3. The method for preparing the A-site reconstructed perovskite oxide according to claim 2, characterized in that: In the step (1), the ratio of LaCoO3, glycerol and isopropanol is 0.3 g: 15-25 mL: 55-65 mL.
4. The method for preparing the A-site reconstructed perovskite oxide according to claim 2, characterized in that: The LaCoO3 is prepared by the following steps: (1) La(NO3)3 and Co(NO3)2 were added to deionized water, and after magnetic stirring for 0.5-1 hour, EDTA and citric acid were added to the above solution, wherein the molar ratio of La(NO3)3, Co(NO3)2, EDTA and citric acid was 1:1:2:4; (2) Stir the solution vigorously and heat it to 90 °C in a water bath. Evaporate the mixed solution until a purple gel is obtained and dry it for 12 h. (3) Grind and calcine the obtained brown spongy solid to obtain the product.
5. The method for preparing the A-site reconstructed perovskite oxide according to claim 4, characterized in that: The calcination in step (3) is divided into two stages, at 5°C min -1 The temperature was raised to 200 °C for 1 h, and then heated at 10 °C min -1 The temperature was raised to 900°C and calcined for 6 hours.
6. Use of the A-site reconstructed perovskite oxide according to claim 1 in catalytic degradation of ENR.
7. The use according to claim 6, characterized in that: Application conditions: ENR concentration is 10 mg·L -1 The catalyst dosage is 0.1 g·L -1 , [PMS] dosage is 0.05-0.3 g·L -1 , the temperature is 295-310K.
8. The use according to claim 7, characterized in that: Application conditions: ENR concentration is 10 mg·L -1 The catalyst dosage is 0.1 g·L -1 , [PMS] dosage is 0.2 g·L -1 , the temperature is 300K.
9. The use according to claim 6, characterized in that: The A-site reconstructed perovskite oxide is loaded on a PVDF substrate to prepare a catalytic membrane for catalytic degradation of ENR, and the ENR solution is degraded by passing through the catalytic membrane under external pressure.
10. The use according to claim 8, characterized in that: The catalyst loading is 5-10 mg, and the flux is 26.45-264.52 L / (m 2 h).
Citation Information
Patent Citations
Method for preparing nano-powder of cathode of solid oxide fuel cell
CN101585558A
Preparation method for modified alumina supporter with high thermal stability
CN103818938A
Graphene oxide rare earth compound catalytic material and preparation method thereof
CN104307530A
LaCoO3@La(OH)3 composite catalyst with relatively high catalytic performance and shell-core structure and preparation method thereof
CN106179368A
Perovskite-type compound metal oxide catalyst and preparation method thereof
CN109364915A